The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.3178/hrl.9.75
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of future runoff projections using Budyko framework and global hydrologic model: conceptual simplicity vs process complexity

Abstract: Abstract:This paper compared future runoff projections using a Budyko type equation with respect to projections by a global hydrological model (GHM). The comparison was made for the annual mean runoff projections for a future period (2060-2100) after the Budyko parameter was set based on hydrologic model outputs at a present period . The objective of this study was to investigate the performance of the Budyko equation with respect to the hydrologic model at different climate regions. To address the question th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Future climate changes projected for catchments in the central Appalachian Mountains region are consistent with other studies that show increases in both P and atmospheric water demand (e.g., [42,92,93]). Changes were greater in magnitude and variability with the more severe RCP compared to the more conservative pathway with lower atmospheric CO 2 equivalents [21,23,24].…”
Section: Twenty-first Century Climate and Streamflowsupporting
confidence: 87%
“…Future climate changes projected for catchments in the central Appalachian Mountains region are consistent with other studies that show increases in both P and atmospheric water demand (e.g., [42,92,93]). Changes were greater in magnitude and variability with the more severe RCP compared to the more conservative pathway with lower atmospheric CO 2 equivalents [21,23,24].…”
Section: Twenty-first Century Climate and Streamflowsupporting
confidence: 87%
“…Comparative studies have shown that Budyko framework-derived methods are robust and effective in hydrological analysis (Zhan et al, 2014;Fernandez and Sayama, 2015).…”
Section: Budyko Framework and Metricsmentioning
confidence: 99%
“…In the midlatitudes of the temperate region where the ''Appalachian Region'' (see section 2) is located, P and E P are of comparable magnitudes (Weiss and Menzel 2008;Fernandez and Sayama 2015). However, E P is directly linked to solar radiation and temperature, which are concentrated in the summer months (Coopersmith et al 2012).…”
Section: Introductionmentioning
confidence: 99%